Catalytic gasification of food waste in supercritical water over La promoted Ni/Al2O3 catalysts for enhancing H2 production. (1st January 2020) - Su, Hongcai; Kanchanatip, Ekkachai; Wang, Defeng; Zhang, Haidan; Antoni,; Mubeen, Ishrat; Huang, Zhicheng; Yan, Mi
Abstract: Ni/Al2 O3 catalyst is the one of promising catalysts for enhancing H2 production from supercritical water gasification (SCWG) of biomass. However, due to carbon deposition, the deactivation of Ni/Al2 O3 catalyst is still a serious issue. In this work, the effects of lanthanum (La) as promoter on the properties and catalytic performance of Ni/Al2 O3 in SCWG of food waste were investigated. La promoted Ni/Al2 O3 catalysts with different La loading content (3–15 wt%) were prepared via impregnation method. The catalysts were characterized using XRD, SEM, BET techniques. The SCWG experiments were carried out in a Hastelloy batch reactor in the operating temperature range of 420–480 °C, and evaluated based on H2 production. The stability of the catalysts was assessed by the amount of carbon deposition on catalyst surface and their catalytic activity after reuse cycles. The results showed that 9 wt% La promoter is the optimal loading as Ni/9La–Al2 O3 catalyst performed best performance with the highest H2 yield of 8.03 mol/kg, and H2 mole fraction of 42.46% at 480 °C. La promoted Ni/Al2 O3 catalysts have better anti-carbon deposition properties than bare Ni/Al2 O3 catalyst, resulting in better gasification efficiency after reuse cycles. Ni/9La–Al2 O3 catalyst showed high catalytic activity in SCWG of food waste and had good stability as it was still active for enhancing H2 production when used in SCWG for the third time, which indicated that La promoted Ni/Al2 O3 catalysts are potential additive to improve the SCWG of food waste. Highlights: H2 production from catalytic gasification of food waste in SCW was studied. Lanthanum promoter was used to improve catalytic efficiency of Ni/Al2 O3 . Ni/Al2 O3 with 9 wt% La loading was determined to be the optimal catalyst. Ni/9La–Al2 O3 could be used for more than three times in SCWG of food waste. Ni/9La–Al2 O3 was better than Ni/Al2 O3 in anti-carbon deposition.